Working-class queers : time, place and politics - Taylor, Yvette, 1978- (Pluto Press, 2023)
"Who cares about working-class queers in Britain today? Are queers marginal to the study of class, and are the working-classes marginal to queer studies? Yvette Taylor critically engages with the experience of working-class queers through cycles of crisis, austerity, recession and migration to show how they have been underrepresented and demands that this changes. Drawing on growing academic, radical activism in queer studies and feminism, she critiques the policy, theory and practice that have maintained queer middle-class privilege at the expense of working-class queers"--